2019
DOI: 10.1177/0040517518824848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sock type on foot health

Abstract: The objective was to determine whether changes in indicators of skin health among participants suffering from diabetes mellitus could be attributable to the type of sock worn (fiber content, structure). Changes in skin health over time (e.g. temperature, skin hardness, transepidermal water loss, stratum corneum hydration) can indicate improvement or deterioration, and these may be related to socks worn. Socks of different structure (single jersey, terry), and of fiber content (merino wool, cotton) were worn ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Work undertaken by Laing et al demonstrated that socks composed primarily of wool can positively affect observable measures of skin health. In addition, merino wool socks maintained their energy-absorbing properties better than cotton socks suggesting they may be beneficial in individuals requiring cushioned socks [30]. This has many potential applications throughout the clinical and consumer healthcare market and is not a new concept; using animal hair in clothing which began to establish a comfort/hygiene trend in the late 1800s, particularly with the idea of moving away from the more extremely-restrictive women's fashion garments of the time, saw the award of a gold medal to Jaeger at the International Health Exhibition in the 1880s [31].…”
Section: Candidate Textile Materials For Medical Applicationsmentioning
confidence: 97%
“…Work undertaken by Laing et al demonstrated that socks composed primarily of wool can positively affect observable measures of skin health. In addition, merino wool socks maintained their energy-absorbing properties better than cotton socks suggesting they may be beneficial in individuals requiring cushioned socks [30]. This has many potential applications throughout the clinical and consumer healthcare market and is not a new concept; using animal hair in clothing which began to establish a comfort/hygiene trend in the late 1800s, particularly with the idea of moving away from the more extremely-restrictive women's fashion garments of the time, saw the award of a gold medal to Jaeger at the International Health Exhibition in the 1880s [31].…”
Section: Candidate Textile Materials For Medical Applicationsmentioning
confidence: 97%